PENGARUH PROFITABILITAS DAN SOLVABILITAS TERHADAP NILAI PERUSAHAAN INDUSTRI MAKANAN DAN MINUMAN YANG TERCATAT DI BURSA EFEK INDONESIA (BEI) - Nurul Azizah Hamzah (Fakultas Ekonomi dan Bisnis, Universitas Muslim Indonesia, 2023)
This study aims to find out that Profibility and Solvency affect Company Value. The object of this study is food and beverage industry companies listed on the Indonesia Stock Exchange in 2019-2023. The method used for sampling is the purposive sampling method, which is a sampling method by paying attention to certain criteria based on the purpose of the research. The type of data in this study is quantitative with secondary data. The data used are the financial statements of 14 food and beverage industry companies listed on the Indonesia Stock Exchange in 2019-2023. The analysis methods used are descriptive analysis, classical assumption test, and multiple linear regression analysis.The results of the research obtained in this test show that the Profitability variable has a positive and significant effect on the Company Value, then Solvency has a negative and significant effect on the Company Value in food and beverage companies listed on the Indonesia Stock Exchange in 2019-2023.